2017
DOI: 10.1038/srep41908
|View full text |Cite
|
Sign up to set email alerts
|

Local entrainment of oscillatory activity induced by direct brain stimulation in humans

Abstract: In a quest for direct evidence of oscillation entrainment, we analyzed intracerebral electroencephalographic recordings obtained during intracranial electrical stimulation in a cohort of three medication-resistant epilepsy patients tested pre-surgically. Spectral analyses of non-epileptogenic cerebral sites stimulated directly with high frequency electrical bursts yielded episodic local enhancements of frequency-specific rhythmic activity, phase-locked to each individual pulse. These outcomes reveal an entrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 75 publications
3
29
0
Order By: Relevance
“…Data obtained at different intensity levels and considering an unequal number of repetitions (at each stimulation intensity) were used from different brain sites of the same patient across distinct patients. A recent study by our group in this same clinical model, showed that regardless of stimulation intensity, intracranial stimulation (with 50 Hz bursts) induced non-statistically significant increases of gamma power 16 . We hence assumed that stimulation intensity would not significantly impact the magnitude of power enhancements generated by electrical pulsed perturbations.…”
Section: Time-frequency Analyses Of Ieeg and Statistical Strategiesmentioning
confidence: 60%
See 3 more Smart Citations
“…Data obtained at different intensity levels and considering an unequal number of repetitions (at each stimulation intensity) were used from different brain sites of the same patient across distinct patients. A recent study by our group in this same clinical model, showed that regardless of stimulation intensity, intracranial stimulation (with 50 Hz bursts) induced non-statistically significant increases of gamma power 16 . We hence assumed that stimulation intensity would not significantly impact the magnitude of power enhancements generated by electrical pulsed perturbations.…”
Section: Time-frequency Analyses Of Ieeg and Statistical Strategiesmentioning
confidence: 60%
“…For each stimulation pulse we extracted 1400 ms of iEEG data (500 ms prior and 900 ms following the onset of each electrical pulse). Data were pre-processed with a pipeline based on in-house programmed software (Matlab, Mathworks, MA, USA) including an artifact removal procedure to eliminate stimulation artifacts 16 and a Laplacian data transformation to estimate local field potentials induced by each electrical pulse 23 . Importantly, only single pulse iEEG data from contacts corresponding to areas classified by an expert epileptologist as non-epileptogenic (i.e., documented as 'healthy' in a clinical report employed later to discuss and plan neurosurgical approaches) were included in our analyses.…”
Section: Intracranial Eeg Data Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with earlier findings and the most current mechanistic understanding of stimulationinduced entrainment (Thut et al, 2011a;Thut et al, 2017), the entrainment phenomenon occurs mainly in a frequency band centered around the stimulation frequency (Thut et al, 2011b;Amengual et al, 2017). On that basis, and also building on our prior experience in the domain Chanes et al, 2015;Quentin et al, 2015;Quentin et al, 2016), our task design and our analytical and statistical strategy were directed to assess changes in oscillatory activity centered in the TMS frequency (30 Hz) delivered to the right FEF.…”
Section: Eeg Recordings and Analysesmentioning
confidence: 69%